Evaluation of Bactericidal Action of Serum Collected from Paratyphoid Patients and Normal Human against Salmonella Paratyphi - Rabbee, Md. Chhanaur; Shahriar, Mohammad; Bhuyian, Mohiuddin Ahmed; Islam, Rishikesh; Islam, Md. Asraful (Dhaka University Journal of Pharmaceutical Sciences, 2013)
A comparative study of susceptibility of clinical isolates of Salmonella Paratyphi to bactericidal action of S. Paratyphi infected human serum and uninfected human serum was investigated. Bactericidal action of S. Paratyphi infected human serum and uninfected human serum was assessed after incubating the bacterial suspension of S. Paratyphi with 40% of both infected and unifected human serum at various incubation times. Eight samples of S. Paratyphi infected serum from the patients diagnosed with paratyphoid fever were used. The investigation found that the serum killed S. Paratyphi both by classical and alternative pathways. Anti- S. Paratyphi antibodies for the bactericidal action of serum were examined by the assessment of bactericidal activity of non-immune normal human serum. Significant killing of S. Paratyphi by S. Paratyphi infected serum was investigated and the serum mediated killing was increased by increasing the incubation time. The mean growth declines gradually as the incubation time was increased. No noteworthy serum mediated killing was observed for normal human serum and inactivated (heat induced) S. Paratyphi infected serum. Dhaka Univ. J. Pharm. Sci. 12(1): 71-75, 2013 (June) DOI: http://dx.doi.org/10.3329/dujps.v12i1.16303